The early Brethren in Christ Church missions and the formation of new identities among the Ndebele in Zimbabwe - Ndlovu, Lovemore (Missionalia, 2021)
This paper examines the impact of the Brethren in Christ Church Christian missions on the spirituality and identity of the Ndebele during the colonial period. Firstly, the paper discusses African religious consciousness prior to the arrival of the Christian missions and then outlines some of the strategies that were employed by the Christian missions, which were geared to transform the image and identity of Africans. Secondly, the paper discusses the aims of the Christian missions in changing the ideology and perceptions of Africans. Consequently, the paper reports on an empirical study conducted in order to determine whether the activities of the Brethren in Christ Church Christian missions led to the formation of new identities. The data obtained from the empirical study demonstrates that the Brethren in Christ Church missionary activities in Zimbabwe greatly transformed the consciousness of the Ndebele - the indigenous modes of perception and practice - resulting in the creation of an early twentieth-century Christian identity.